BIOPOLIMER DARI KITOSAN-COLLAGEN UNTUK APLIKASI PEMBALUT LUKA DENGAN CMC DAN GLUKOMANAN SEBAGAI BAHAN IKAT SILANG - Laksita Ika Paksi; Suryati Suryati; Agam Muarif; Narul ZA; Meriatna Meriatna (Jurnal Teknologi Kimia Unimal, 2023)
Wound dressing is a nursing action to protect the wound by closing the wound, which can be done using sterile gauze that is not attached to the wound tissue. Currently, commonly used wound dressings are made of polymeric materials. Polymers for wound dressings consist of absorbents in contact with the wound. The absorbent layer will protect the wound and absorb the liquid that comes out of the wound. The purpose of this study is to make a biopolymer derived from chitosan, collagen and its cross-binding materials, namely CMC and glucomannan, and to find out the correct composition comparison to produce an ideal biopolymer. The method is drying in the oven on a thin glass printer for 24 hours. Mixing all raw materials with chitosan volume:collagen: CMC and chitosan:collagen: glucomannan in a ratio of 50:50:2,5; 50:50:5; 50:50:7,5; and 50:50:10. Then put in the oven with a temperature of 60⁰C during for 48 hours. The biopolymers formed are then tested to determine the characteristic properties of the biocomposites formed. The analysis carried out is FTIR group analysis, swelling analysis, absorption test and membrane thickness test. The results of the study with the comparison of chitosan: collagen: CMC and chitosan : collagen: glucomannan for the analysis of the FTIR group of the biopolymer membrane contains compounds (O-H), C-H, C =O, C-O-C, CH2, CN, and CH, for swelling tests on CMC additives the value obtained is 73%; 82%; 79%; 105% while for glucomannan additives, a result of 32%; 57%; 65%; and 51%, for absorption test on additives CMC the value that can be obtained is 125%; 176%; 285%; 233%; while for glucomannan additives, a yield of 97%; 96%; 90%; and 86% and for membrane thickness test additives CMC the value in can be 0.94 mm; 0.79 mm; 1.06 mm; 1.32 mm; while for glucomannan additives, the result is 1.3 mm; 1.58 mm; 1,6 mm; 1.67 mm.